2012
DOI: 10.29059/cienciauat.v7i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Revisión de la clasificación de braconidae (1900-2012): Subfamilias en México

Abstract: RESUMENLos bracónidos son avispas parasitoides que se han utilizado con éxito en muchos programas de control biológico de insectos plaga a nivel mundial. En la presente revisión, se analiza la clasificación de las subfamilias de Braconidae, cuyo cambio ha sido notable durante las últimas dos décadas, también se registran los géneros que cambiaron de subfamilia en ese período. En México se registran actualmente 35 subfamilias (28 en el Museo de la UAT), 318 géneros y 704 especies. Sin embargo, aún existe gran c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Members of the subfamily Cheloninae have been used in the biocontrol of exotic pests ( Narendran 2001 ). In Mexico, 704 species of Braconidae have been listed from 34 subfamilies ( Coronado-Blanco et al 2012 ), of which, only 17 species of Cheloninae have been identified ( Coronado-Blanco and Zaldívar-Riverón 2014 ). However, most of these species belong to the genus Chelonus Panzer, 1806 ( Coronado-Blanco et al 2004 ), which is well known to control the populations of the fall armyworm Spodoptera frugiperda (J.E.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the subfamily Cheloninae have been used in the biocontrol of exotic pests ( Narendran 2001 ). In Mexico, 704 species of Braconidae have been listed from 34 subfamilies ( Coronado-Blanco et al 2012 ), of which, only 17 species of Cheloninae have been identified ( Coronado-Blanco and Zaldívar-Riverón 2014 ). However, most of these species belong to the genus Chelonus Panzer, 1806 ( Coronado-Blanco et al 2004 ), which is well known to control the populations of the fall armyworm Spodoptera frugiperda (J.E.…”
Section: Discussionmentioning
confidence: 99%